A reassessment of the Renealmia chrysotricha (Zingiberaceae) species complex based on morphological evidence and nomenclatural notes - Lima, Helena Regina Pinto; Gevú, Kathlyn Vasconcelos; Andreata, Regina Helena Potsch; Braga, João Marcelo Alvarenga (Phytotaxa, 2018)
Based on field observations of several natural populations of Renealmia chrysotricha (Zingiberaceae) in the Brazilian Atlantic Forest and comparison with other specimens in different herbarium collections, the morphological circumscription of this species was broadened with the inclusions of Alpinia humilis, R. angustifolia, R. brasiliensis, R. longipes, R. petasites, and R. reticulata as synonyms. The expanded analysis of the morphological characteristics, such as the presence of sessile leaves, reticulation patterns of its leaf-sheaths, flowers with short pedicels, and membranous bracts, suggest that these species share the same characteristics used to circumscribe them.